Towards sustainable management of sharks and rays in the Bay of Bengal, Bangladesh - Haque, AB (2023)
Elasmobranchs (hereafter referred to as 'sharks and rays') have declined in landings, species diversity in catch and population size in various regions of the world due to human-driven pressures, primarily unsustainable fishing. Combined with their life history characteristics, these pressures make them extremely vulnerable to ongoing threats. Incidental shark and ray catches (or bycatch) are substantial and essential livelihood options for food security in developing countries. Considerable shark and ray catches and traded products come from countries marked by the perpetual poverty of coastal communities that depend highly on artisanal fisheries. This doctoral research takes the case study of shark and ray fisheries in Bangladesh to understand the key issues and to investigate potential practical conservation and management actions for sharks and rays from a global south perspective. Artisanal fisheries in the Bay of Bengal of Bangladesh contribute to the worldwide fishing pressure on sharks and rays. However, it is also one of the most data-poor regions of the world. Here, the fisheries are heterogeneous and complex, and socio-economic dependence is high, making it extremely challenging to balance fish protection and fishers' livelihoods. I addressed the lack of critical data on sharks and ray fisheries in Bangladesh, considering species diversity, fishery characteristics and trade in detail through a combination of field surveys, observations, and interviews. I also evaluated the risks of different shark and ray species against contemporary fishing pressures by assessing species’ ‘area of exposure’ to artisanal fishing. Key findings include the high diversity of sharks and rays within the artisanal landings. However, decreased diversity, abundance, and size of caught specimens was also revealed, attributed to increased fishing intensity, and an accessible market. Furthermore, most southwestern and southcentral shallow waters were found to have a high risk of species encounter with artisanal fisheries; thus, spatiotemporal management needs to be prioritised, particularly in these areas. Gillnet fishing was found to be the most significant threat to bycatch sharks and rays due to its three- dimensional spatial scale and fishing tactics. While the catch and trade of most sharks and rays are regulated under Bangladesh's law, this study revealed an absence of bycatch mitigation strategies and no incentives for fishers to adhere to current laws leading to non- compliance. Likely causes of non-compliance include a dearth of awareness, alternative livelihoods, technical facilities, and the complex nature of the fisheries. Lack of opportunities and information to adhere to regulations and increased enforcement (only) has led to conflicts, non-compliance and unwillingness to report catches by fishers and traders. An imbalanced power and financial structure between actors (e.g., fishers, traders) were also revealed, with actors accessing unequal benefits from the market. Impediments for implementing conservation measures by low-access actors (e.g., fishers) with limited decision-making power or resources were evident. Fishers reported several socio-ecological, technical, and enforcement issues (e.g., policing instead of meaningful monitoring and punitive measures without facilitating compliance). Crucial interventions to address the unsustainability problem include improved taxonomic research, enhanced monitoring of stocks, meaningful protection for threatened taxa and safeguarding fishers to improve compliance. Although legal measures are necessary, this cannot be the only tool to mitigate the significant cumulative effects of fishing on these species. Reducing the risk from fisheries requires pre-emptive measures that minimise the interaction of species with fisheries through improved and better- informed careful management. Encouraging and facilitating the engagement of fishers in science (data collection), local governance (policy-making), and field implementation (bycatch mitigation) is vital, acknowledging that adequate time and resources will be required to change practices. A key recommendation is to focus management efforts in specific coastal locations (i.e., evidence-based spatiotemporal management) while prioritising high-risk species groups benefitting multi-taxa conservation. These interventions must be rooted in sustainable approaches and co-designed with fishers, with appropriate training and resources available.